3448 Macrophages, APOL1 Genotype, & Immunometabolism in CVD (MAGIC. (27th March 2019) - Blazer, Ashira D.; Chang, Miao; Robins, Kimberly; Buyon, Jill; Clancy, Robert
Abstract : OBJECTIVES/SPECIFIC AIMS: This study aims to understand the potential immunomudualtory effect of APOL1 variants in auto-antigen activated myeloid cells by assessing lysosomal integrity in activated cells expressing APOL1. The primary stimuli were: 1. ssRNA hY3 as a proxy for the Ro immune complex; 2. in an bulk RNA seq model, interferon-response gene, Siglec 1, as a read out of interferon activity. The primary outcomes were: 1. Myeloid cell APOL1 expression both in primary macrophage cultures and ex-vivo patient derived macrophages; 2. Lysosome integrity as measured by fluorescence intensity of lysotracker dye on light microscopy. METHODS/STUDY POPULATION: All recruited subjects provided written informed consent as per the NEW YORK UNIVERSITY Division of Rheumatology-wide Specimen and Matched Phenotype Linked Examination (SAMPLE) protocol. Subjects were African American; SLE subjects met 4 American College of Rheumatology criteria for SLE. Healthy donor monocytes representing each genotype in duplicate (reference allele: G0/G0; heterozygote variant: RV/G0; and homozygote variant RV/RV) were cultured with GM-CSF to yield macrophages which were incubated in serum free media or with hY3 ssRNA (TLR 7/8 agonist) to yield inflammatory M1 macrophages. Fold increase of APOL1 in untreated vs hY3 treated macrophages was measured using qPCR. Live cells were then cultured on glass chamber slides with DNA dye, DAPI, and Lysotracker red, a fluorescent dye that stains acidic lysosomes. As a proof of concept, interferon response gene, Signlec1, and APOL1 transcriptional activity in peripheral blood monocytes (PBMCs) were measured and correlated in 17 SLE patients by RNA seq. RESULTS/ANTICIPATED RESULTS: Regardless of genotype, hY3 increased APOL1 expression by 29 (+/−18.4) fold (P = 0.007 vs no treatment). Genotyping of the qPCR product showed concordance with the chromosomal DNA with the RV heterozygotes expressing both alleles. To examine lysosomal membrane integrity, live hY3-treated macrophages were stained with lysosotracker dye and fluorescence intensity was measured. Compared to reference allele carrying macrophages, each additional variant allele corresponded with a lesser degree of lysosome compartment staining. In SLE PBMCs, we found that APOL1 was highly expressed, and significantly correlated with Siglec1 (F=10.5; P = 0.005) supporting an association between circulating interferons and APOL1 accumulation in monocytes. DISCUSSION/SIGNIFICANCE OF IMPACT: Given that the "cytokine milieu" in SLE elicits APOL1 expression, induces inflammatory cell metabolic rewiring, and stimulates autophagy thereby exposing defects in autophagic flux, this gene-environment interaction may underpin the relationship between chronic inflammation and heightened APOL1 polymorphism-attributed cardiovascular risk. These data support further inquiry into the intersection between chronic autoimmunity and APOL1's functional role in the vascular microenvironment. The in vitro studies herein extend our prior work by demonstrating a mechanistic link between SLE-associated inflammation, APOL1 risk variant status and CVD via a lysosomal defect which converges on common autophagic and metabolic pathways in mononuclear cells.